Dawr al-Ḥarakāt al-Nisā’īyah fī I’ādat Taskhīl Qānūn al-Mujtama’ al-Islāmī bi Indūnīsīyā - Khoiruddin Nasution (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
This article deals with the role of the Indonesian women's movement in the reformation of Indonesian Islamic marriage law. The author took an historical approach in conducting the research; hence the main sources are the books and articles that contain the historical record of the events concerned. The study shows that the role of the Indonesian Women's Movement is very significant in the reform of Indonesian marriage law. The birth of the Indonesian feminist movement is said to date back to the 1900's, since it was intimately allied to the national awakening. Raden Ajeng Kartini, who lived from 1879 to 1904, was the first woman to privately demand the emancipation of women. However she was principally concerned with improving women's participation by means of education, such as learning household duties, dress-making classes, course of child welfare, and the like. Rohana Kudus in Minangkabau, West Sumatra, was the first woman who privately and directly criticized the bad effects of child marriage, polygamy and one side divorce.DOI: 10.15408/sdi.v8i2.691